The role of intergenerational family in family functions and cultural values in Aligudarz, Iran in 2022 - Mohsen Esmaeili; Omid Ali Ahmadi; Ali Roshanaei; Mohammad Hossein Asadi Davoodabad (Shahid Beheshti University of Medical Sciences, 2023)
Background: Based on diversified intergenerational living in urban Iran, this study was conducted to determine the role of intergenerational family in family functions and cultural values in Aligudarz. Methods: This study was analytical cross-sectional based on questionnaire. The population were included over 18 years of age in Aligudarz, 376 people were selected as a sample using Cochran sampling by simple random sampling method. Library and survey methods were used to collect data. One-way analysis of variance and Pearson correlation tests were used to test the hypotheses. Results: Elderly people have better family functions than others (P=0.011) and adhere more to cultural values. Elderly people have more management in family crises with f value of 3.140 (p=0.019). The correlation coefficient between family cohesion and family functions is 0.152 with a direct correlation (P=0.003). As the level of family cohesion increases, family functions also increase. There is a direct correlation between kinship relations and family functions (P=0.777, -0.015). There is no relationship between the level of kinship and family functioning. Conclusion: It is possible to improve the current status given the level of adherence to cultural values, crisis management, and family cohesion, Kinship relationships among different generations, and the relationship between the variables of adherence to cultural values, crisis management and cohesion, and family functions.